2019
DOI: 10.1590/s1984-29612019040
|View full text |Cite
|
Sign up to set email alerts
|

Fascioliasis in buffaloes: A 5-year forecast analysis of the disease based on a 15-year survey in Brazil

Abstract: In South America, fascioliasis caused by the trematode Fasciola hepatica is an anthropozoonosis disease associated with significant economic losses and poor animal welfare. The objective of this study was to determine the prevalence of F. hepatica in the liver of buffaloes slaughtered from 2003 to 2017 in Brazil, and to perform a forecast analysis of the disease for the next five years using the Autoregressive Integrated Moving Average (ARIMA) model. Data analysis revealed an incidence of 7,187 cases out of 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The metacercariae is ingested during feeding when animals are pasturing or humans eat contaminated vegetables or water (Toledo et al, 2012). Fascioliasis is considered to be endemic in many countries of Latin America (Carmona & Tort, 2017;Pritsch et al, 2019a), and occurs mainly in livestock in the South of Brazil (Bennema et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The metacercariae is ingested during feeding when animals are pasturing or humans eat contaminated vegetables or water (Toledo et al, 2012). Fascioliasis is considered to be endemic in many countries of Latin America (Carmona & Tort, 2017;Pritsch et al, 2019a), and occurs mainly in livestock in the South of Brazil (Bennema et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“… Aleixo et al (2015) also registered the presence of cattle slaughtered and condemned for fasciolosis in the states of Pará and Tocantins, and Almeida et al (2024) reported cases in the Northeast region, confirming the expansion of this trematode throughout Brazil. The presence of F. hepatica in sheep, goats and buffaloes has been recorded so far in the South and Southeast regions ( Carneiro et al, 2013 ; Pritsch et al, 2019 ; Serra-Freire & Nuernberg, 1992 ).…”
Section: Distribution and Epidemiologymentioning
confidence: 99%
“…Studies of sheep and buffaloes are less common, but Cunha et al (2007) registered a rate of 8.87% condemnation of sheep in Rio Grande do Sul. Moreover, Pritsch et al (2019) reported an average national prevalence of 3% in buffaloes between 2003 and 2017, with averages of 11.9% in Paraná and 7.7% in Rio Grande do Sul.…”
Section: Distribution and Epidemiologymentioning
confidence: 99%
“…is lower in South Eastern Iran than has been reported elsewhere in the world. For instance, in Brazil a rate of 11.9% (Pritsch et al., 2019) was reported in livers of buffaloes slaughtered from 2003 to 2017. This rate was 2.17% in dairy cattle slaughtered during 2015 and 2016 in Portugal (Barbosa et al., 2019).…”
Section: Discussionmentioning
confidence: 99%